Vulvar sarcomatoid squamous cell carcinoma: A rare entity - Gayatri Gund; Akansha Chadha; Atul Dongre; Chitra Nayak (Wolters Kluwer Medknow Publications, 2023)
Vulvar squamous cell carcinoma with sarcomatoid features is an extremely rare histological variant of squamous cell carcinoma with co-existence of both epithelial and mesenchymal features. A 70-year-old woman presented with genital lesions for 4 months with associated burning and pain. Examination revealed well-defined bilaterally symmetrical hyperpigmented plaques on labia majora, fleshy erythematous growth on labia minora. Biopsy from the fleshy mass was suggestive of sarcomatoid malignancy. However, immunohistochemistry was positive for cytokeratin AE1/AE3 and negative for desmin and smooth muscle actin. Biopsy from hyperpigmented plaque was suggestive of Bowens disease. On the basis of histopathology and immunohistochemistry findings, diagnosis of vulvar sarcomatoid squamous cell carcinoma with Bowens disease was made and patient was started on external beam radiation therapy. Sarcomatoid squamous cell carcinoma of vulva is very rare cancer that has an aggressive and fatal course. Diagnosis has traditionally been difficult due to a large ratio of sarcomatous to squamous cell component. Due to its rarity, there are no distinct guidelines to direct therapy and care.